2021
DOI: 10.1051/e3sconf/202131401002
|View full text |Cite
|
Sign up to set email alerts
|

Technical Economic study for Electricity Production by Using (Tidal-Hydrogen) in Socotra Island, Yemen

Abstract: The great need to use electricity at present and to ensure its continuity in future requires finding renewable and sustainable sources; the best of those sources are renewable energy sources such as wind energy, solar energy, and tides. All research focuses on studying those sources for each region to give the complete database that can rely upon in future to build projects generating electric power according to accurate scientific studies, specifically in areas far from the main electricity grid, such as remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Thus, Serag et al (2021) proposed that tidal energy be implemented in Socotra. “Tidal energy is a type of renewable energy source, as tidal movement in oceans is converted into electrical energy by tidal turbines” (Serag et al, 2021, pg. 2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, Serag et al (2021) proposed that tidal energy be implemented in Socotra. “Tidal energy is a type of renewable energy source, as tidal movement in oceans is converted into electrical energy by tidal turbines” (Serag et al, 2021, pg. 2).…”
Section: Discussionmentioning
confidence: 99%
“…While searching for information on the Socotra economy, I found no academic papers or any other reports. Some economic studies can be found about electricity production in Socotra (Alkaf et al, 2010; Serag et al, 2021), and those are the only accessible studies related to the economy of Socotra. It does not come as a surprise that the island suffers from electricity shortages (Alkaf et al, 2010), which I experienced while there.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, the production costs of green H 2 from PV and wind energy remained the highest, with an estimated 3.64 USD/kg H2 . Serag et al [52] performed a techno-economic study on the production of green H 2 using a PEM electrolyzer powered by the tidal movement in the oceans surrounding the Socotra Islands in Yemen. The assessment results showed that the production cost of H 2 was 9 USD/kg H2 , with most of the fault being due to the high electricity costs.…”
Section: High Production Costsmentioning
confidence: 99%
“…Figure 6 illustrates the potential for cost reduction in current AWE and PEM electrolysis by combining several stacks to increase the capacity of the overall system, according to the IEA [36]. In IRENA's 2020 report "Green hydrogen cost reduction: scaling up electrolyzers to meet the 1.5 • C climate goal" [52], a detailed analysis of strategies for cost reduction at stack and system levels of electrolyzers, along with their associated challenges and benefits, is presented.…”
Section: Expected Decrease In Electrolyzer and Renewable Energy Costsmentioning
confidence: 99%